Neither liberty nor safety : fear, ideology, and the growth of government - Higgs, Robert (Independent Institute, 2007)
The history of the United States, from the 19th century to present day, is included in this examination of the very foundations of unwarranted government intrusiveness that illuminates the two essential elements that have led to the expansion of the state's authoritythe ideology that the government should serve as a savior whenever people face threats to their well-being and the public fear that follows the perception of a large-scale threat to peace or prosperity. When these two factors operate simultaneously, people demand that the government take protective measures on their behalf. Hence, in an outburst of opportunism, the growth of government accelerates during the crisis, at the expense of liberty. Dr. Higgs's conclusion is undeniable: placing confidence in the government to function as savior or problem solver does not lead to the peace, prosperity, and safety that people crave. On the contrary, that misplaced confidence ultimately leads to tyranny and diminished securityin Benjamin Franklin's words, Neither liberty nor safety.